Acupuncture for type 2 diabetes mellitus with nonalcoholic fatty liver disease: A protocol for systematic review and meta-analysis. Issue 21 (28th May 2021) - Li, Mengyuan; Yao, Lin; Huang, Haipeng; Wang, Guan; Yu, Bin; Zheng, Haizhu; Wang, Hongfeng
Abstract: Background: T2DM with NAFLD is a common disorder of glucose and lipid metabolism affecting the quality of life of patients. Due to the limitations and adverse reactions of drug treatment, acupuncture has been proved to be an effective method for the treatment of T2DM with NAFLD. This study aims to evaluate the efficacy and safety of acupuncture in the treatment of NAFLD in T2DM class, and to provide high-quality evidence for acupuncture in the treatment of this disease. Methods: From establishment of the database to 31 July 2021, We will search the Cochrane Central Register of controlled trials, PubMed, MEDLINE, EMBASE, Web of science. Five Chinese databases, including China National Knowledge Infrastructure (CNKI), WanFang database, VIP, Chinese Biomedical Literature Database (CBM) and the Chinese clinical trial registry. There are no restrictions on language or publication, and they are independently screened and collected by two reviewers. Review Manager 5.3 software will be used for meta analysis. If necessary, heterogeneity testing, data synthesis, and subgroup analysis will be performed. Results: The effectiveness and safety of acupuncture in the treatment of T2DM with NAFLD will be assessed by the outcomes of test's, including: imaging indicators, biomarkers of hepatic steatosis, serological indicators of hepatic fibrosis, improvement of serum NAFLD liver fat score, BMI, blood glucose indexes, blood lipid indexes, insulin level and safety indicators. Conclusion: This meta-analysis will further determine the beneficial efficacy and safety of acupuncture for T2DM combined with NAFLD.